Peran Hukum Terhadap Perjanjian Kredit Dalam Jaminan Hak Tanggungan - Ridha, Irfan; Kurniawan, Nauval Fajar; Artati, Nindi Restu; Nugraha, Novi Yuzti; Regina, Putri; Wulan, Rezka; Akbar, Ricko Fadila Akbar7; Ramdhanti, Siti; Purwati, Silvi Andini; S, Salsabila; Amanda, Vykha Nurulloh Mardiyah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This writing aims to identify the role and position of the creditor in a situation where the debtor violates the mortgage agreement. Legal protection for creditors when debtors violate agreements or do not fulfill promises can be found in the form of documents such as authentic deeds or private statements regulated by Law Number 4 of 1996, as explained in Article 10. The approach used in this writing is type law that is based on norms and is descriptive. The data used in this research comes from secondary sources, through literature study and analysis of various books and data sources available on the internet. The results of this research reveal cases of default or breach of promise made by customers. Thus, this paper aims to understand the legal role of the creditor as the holder of the main mortgage rights in a credit agreement that is violated or not fulfilled by the debtor.